Beginning Git and GitHub : a comprehensive guide to version control, project management, and teamwork for the new developer - Tsitoara, Mariot (Apress, 2020)
Learn the fundamentals of version control through step-by-step tutorials that will teach you the ins-and-outs of Git. This book is your complete guide to how Git and GitHub works in a professional team environment. Divided into three parts - Version Control, Project Management and Teamwork - this book reveals what waits for you in the real world and how to resolve the problems you may run into. Once past the basics of Git, you'll see how to manage a software project, and finally how to utilize Git and GithHub to work effectively as a team. You'll examine how to plan, follow and execute a project with GitHub, and then apply those concepts to real-world situations. Workaround the pitfalls that most programmers fall into when driving a project with Git by using proven tactics to avoid them. You will also be taught the easiest and quickest ways to resolve merge conflicts. A lot of modern books on Git don't go into depth about non-technical topics. Beginning Git and GitHub will help you cover all the bases right at the start of your career.